2006
DOI: 10.1161/circulationaha.105.575340
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Wave Fractionation at Boundaries of High-Frequency Excitation in the Posterior Left Atrium of the Isolated Sheep Heart During Atrial Fibrillation

Abstract: Background-High-frequency fractionated electrograms recorded during atrial fibrillation (AF) in the posterior left atrium (PLA) and elsewhere are being used as target sites for catheter ablation. We tested the hypothesis that highly periodic electric waves emerging from AF sources at or near the PLA give rise to the most fractionated activity in adjacent locations. Methods and Results-Sustained AF was induced in 8 isolated sheep hearts (0.5 mol/L acetylcholine). Endocardial videoimaging (DI-4-ANEPPS) and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
271
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(301 citation statements)
references
References 30 publications
24
271
1
5
Order By: Relevance
“…It is noteworthy that, in our population, spectral turbulence, starting during the first seven days in sinus rhythm, was mostly concentrated in the terminal portion (second half, Figure 2) of the P-wave. The temporal relationship of the high-frequency content detected on the P-wave in the present study is in accordance, at least in part, with the high-frequency fragmentation registered in left atrium during atrial fibrillation by Kalifa et al 33 .…”
Section: (B) Mec (%) (C) Sec (%) (D) Met (Hz) (E) Set (Hz)supporting
confidence: 93%
See 1 more Smart Citation
“…It is noteworthy that, in our population, spectral turbulence, starting during the first seven days in sinus rhythm, was mostly concentrated in the terminal portion (second half, Figure 2) of the P-wave. The temporal relationship of the high-frequency content detected on the P-wave in the present study is in accordance, at least in part, with the high-frequency fragmentation registered in left atrium during atrial fibrillation by Kalifa et al 33 .…”
Section: (B) Mec (%) (C) Sec (%) (D) Met (Hz) (E) Set (Hz)supporting
confidence: 93%
“…Other studies have demonstrated a strong correlation between fractionated endocardial electrograms and AF episodes 33,34 . Fragmented ventricular activation detected by endocardial electrograms has been already correlated with low-amplitude and high-frequency signals detected on body surface SAECG 35,36 .…”
Section: (B) Mec (%) (C) Sec (%) (D) Met (Hz) (E) Set (Hz)mentioning
confidence: 87%
“…It has been further proposed that these fractionated sites are important in sustaining AF, 53 and that targeting fractionated electrograms with ablation can terminate AF and prevent its re-induction or recurrence. 52,[54][55][56][57][58][59][60] The data supporting these conclusions are rather weak overall, with only a few small, randomised clinical trials providing guidance, and different studies have arrived at disparate conclusions regarding the importance, or lack thereof, of fractionated electrograms in the pathogenesis of AF.…”
Section: Limitations Of Targeting Rotors With Ablation For the Treatmmentioning
confidence: 99%
“…5 To further rationalize the use of CFAE and DF for ablation guidance, Kalifa et al demonstrated in isolated sheep hearts that these two measures may be predictably organized, whereby the most fractionated activity is found at the periphery of a source region having the highest activation rate. 8 In addition, experimental 9;10 and clinical 11 mapping studies have indicated that functional reentry underlies the highest activation rate and the maintenance of AF. However, the relationship between the spatiotemporal stability of such reentrant drivers and the fractionation and rate of the activation in their periphery has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%